Case Report: Invasive fungal infection after anti-CD19 CAR-T cell therapy. Implication for antifungal prophylaxis - Pennese, Elsa; Salutari, Prassede; Carriero, Luigi; Restuccia, Francesco; De Filippis, Antonio Fabio; De Luca, Giulia; Giancola, Raffaella; Guardalupi, Francesco; Corradi, Giulia; Fabi, Bianca; Baldoni, Stefano; Di Ianni, Mauro (Frontiers in Immunology, 2023)
CAR-T therapy has revolutionized the treatment of relapsed/refractory B-cell malignancies. Patients who are receiving such therapy are susceptible to an increased incidence of infections due to posttreatment immunosuppression. The need for antifungal prophylaxis during the period of neutropenia remains to be determined. The clinical outcome of a 55-year-old patient with relapsed/refractory DLBCL who received axicabtagene ciloleucel is described here. The patient developed CRS grade II and ICANS grade IV requiring tocilizumab, prolonged use of steroids and anakinra. An invasive pulmonary aspergillosis arose after 1 month from CAR-T reinfusion, resolved with tracheal sleeve pneumonectomy. The patient is now in Complete Remission. This case suggests that antifungal prophylaxis should be considered. We have now included micafungin as a standard prophylaxis in our institution.